Optimal System and Invariant Solutions of the Hyperbolic Geometric Flow (Journal of Mathematical Study, 2022)
By analyzing Lie symmetric algebra of the hyperbolic geometric flow, the one-dimensional optimal system of the symmetries to the equation is obtained, and we use similarity reduction to find the reduced equation. By solving the reduced equations, the invariant solutions of the hyperbolic geometric flow are finally obtained.